Environment-friendly high-stability soldering flux and preparation method thereof
By using triethanolamine and cyclohexane citric acid in the flux, the combination of ethyl orthosilicate and vinyl triethoxysilane, combined with the combination of magnesium fiber, the problem of insufficient stability and wettability of flux is solved, and an efficient and environmentally friendly welding effect is achieved.
Patent Information
- Application Number
- CN202411860951.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing fluxes are prone to produce toxic and harmful substances during use, leading to environmental pollution and fire explosion risks, and insufficient stability and infiltration ductility, affecting welding quality.
Triethanolamine and cyclohexane citric acid are used to combine the synergistic effect of Vaseline to increase the antioxidant resistance; ethyl orthosilicate is used to combine with vinyl triethoxysilane to form activated silicon spheres and cooperate with magnesium fibres to improve the infiltration ductility and stability.
It effectively prevents the formation of oxide film on the surface of the welded parts, reduces the generation of bubbles and smoke, significantly improves the stability and insulation of flux, improves welding quality, and is environmentally friendly and has a small odor, which is suitable for large-scale production.
Smart Images

Figure CN119609459A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soldering flux, and in particular to an environmentally friendly high-stable soldering flux and a preparation method thereof. Background Art
[0002] Soldering is the main process in electronic assembly. Flux is an auxiliary material to ensure the smooth progress of the welding process. The main function of flux is to remove oxides on the surface of solder and the base material to be welded, so that the metal surface reaches the necessary cleanliness. It prevents the surface from re-oxidation during welding, reduces the surface tension of the solder, and improves the welding performance.
[0003] The quality of flux performance directly affects the quality of electronic products. With the rapid development of industrial production, the requirements for welding effects are getting higher and higher. Existing fluxes are prone to produce toxic and harmful substances during use, which can easily cause environmental pollution. If they encounter open flames or high-temperature heat sources, they can easily cause fires or explosions. At the same time, in actual use, they are often required to have better stability and wetting ductility.
[0004] CN101157168A discloses a rosin-type halogen-free, cleaning-free soldering flux for lead-free solder wire, which is composed of the following substances in percentage by mass: 4-18% organic acid activator, 10-30% organic solvent, 1-6% paste-forming agent, 0.2-3% stabilizer, 0.5-5% thixotropic agent, 0.5-4% surfactant, 0.5-5% corrosion inhibitor, and modified rosin as the balance: the soldering flux does not contain halogen and has a high insulation resistance after welding, but its paste-forming agent uses one or more of polyethylene glycol 2000, polyethylene glycol 4000 or polyethylene glycol 6000, and polyethylene glycol will undergo thermal decomposition during the welding process, and its products are all volatile, so the smoke is large during the welding process, which is harmful to human health to a certain extent and will pollute the environment.
[0005] CN104117787A discloses an environmentally friendly no-clean soldering flux, which includes the following components by mass percentage: 1.0-4.0% aspartic acid, 0.4-1.0% lactic acid, 0.4-1.2% gallic acid, 2-8% ethyl lactate, 5-15% ethanol, 6-12% glycerol, 0.3-1.5% propylene glycol monomethyl ether propionate, 0.4-2.2% surfactant, 0.2-1.6% corrosion inhibitor, and the balance is deionized water. The environmentally friendly no-clean soldering flux is made of deionized water as solvent, aspartic acid, lactic acid and gallic acid as activators, ethyl lactate, ethanol and glycerol as cosolvents, and propylene glycol monomethyl ether propionate as a film-forming agent. The soldering flux meets environmental protection requirements, but under high temperature conditions, the components in the soldering flux are easy to change, the activator is easy to decompose, and the stability is poor.
[0006] CN 108098189 A discloses an environmentally friendly soldering flux, comprising the following components in parts by weight: 15-30 parts of hydrogenated castor oil, 80-150 parts of disproportionated rosin, 100-120 parts of epoxy resin, 10-15 parts of nano calcium oxide, 10-30 parts of acetone, 20-30 parts of organic esters, 5-30 parts of o-hydroxybenzoic acid, 50-80 parts of organic ether and 0.5-2.5 parts of benzotriazole. The soldering flux prepared by hydrogenated castor oil and nano calcium oxide, as well as the combination of disproportionated rosin and other substances, does not contain lead and halogen, and has little pollution to the environment. However, the rosin derivatives of the soldering flux are volatile substances, which will produce bubbles and affect the welding quality. At this time, the soldering flux with high viscosity will make it difficult for the oxide to diffuse, increase the pressure of the bubbles, and cause more bubbles to be generated, further affecting the quality of the solder joint.
[0007] At present, the quality of cast welding is closely related to the flux. At present, the flux is not only easy to pollute the environment, but also has certain harm to human health. At the same time, the stability and wetting ductility are poor, which affects the cast welding effect, making the use effect of the flux generally mediocre. Therefore, how to propose an environmentally friendly flux to solve the above problems has become a technical problem that needs to be solved at present. Summary of the invention
[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an environmentally friendly radiation-proof coating for construction and a preparation method thereof.
[0009] The invention discloses an environmentally friendly high-stable soldering flux. The raw materials include, by weight, 8-10 parts of triethanolamine, 3-5 parts of vaseline, 5-8 parts of cyclohexane citric acid, 0.1-1 parts of corrosion inhibitor, 5-8 parts of solvent, 1-3 parts of coumarone resin, 5-8 parts of hydroxy acrylic resin, 1-2 parts of vinyl triethoxysilane, 2-6 parts of ethyl orthosilicate, 1-2 parts of cholesterol, 0.1-0.5 parts of phospholipid, 0.1-0.3 parts of diisopropylbenzene peroxide, 1-3 parts of polyamide monomer, 3-5 parts of brucite fiber, 0.5-1.0 parts of sodium stearate, 1-2 parts of hydrogenated castor oil and 1-2 parts of zinc dichloride.
[0010] Preferably, the corrosion inhibitor is rosin amine imidazoline.
[0011] Preferably, the solvent is at least one of methanol, ethanol, ethyl acetate and propylene glycol.
[0012] Preferably, the polyamide monomers include linolenic acid and ethylenediamine, and the weight ratio of linolenic acid to ethylenediamine is 1-2:1-2.
[0013] Preferably, the brucite fiber has a particle size of 20-30 nm and an aspect ratio of 20-25:1.
[0014] Preferably, the phospholipid is lecithin.
[0015] The above-mentioned method for preparing the environmentally friendly and highly stable soldering flux comprises the following steps:
[0016] S1. Mix triethanolamine, vaseline, cyclohexane citric acid, corrosion inhibitor and solvent, and stir at a temperature of 40-50° C. for 10-20 min to obtain preform a;
[0017] S2, mixing coumarone resin and hydroxy acrylic resin, stirring at a temperature of 90-100° C. for 20-30 min, cooling to 40-50° C., adding to prefabricated material a and stirring evenly to obtain prefabricated material b;
[0018] S3, adding vinyl triethoxysilane, ethyl orthosilicate, cholesterol, and phospholipids to chloroform, stirring evenly, removing chloroform by rotary evaporation, adding to phosphate buffer, ultrasonicating at a temperature of 10-30°C for 1-2h, using an extruder to pass through a filter membrane with a pore size of 100-500nm to a pH value of 8-9 ammonia solution, standing at a temperature of 50-60°C for 15-30h, centrifuging, washing, and vacuum drying to obtain activated silica balls;
[0019] S4, adding activated silica balls and dicumyl peroxide to ethanol and stirring evenly, adding polyamide monomer thereto, reacting at a temperature of 65-75° C. for 20-24 h under nitrogen protection, centrifuging, washing with water 2-3 times, and vacuum drying to obtain polyamide silica composite microspheres;
[0020] S5. Add brucite fiber and sodium stearate into water and stir for 1-2h, add silica composite microspheres, ultrasonicate at 40-50℃ for 1-2h, cool to room temperature, filter, wash, vacuum dry, crush, add hydrogenated castor oil, zinc dichloride and preform b and mix well to obtain environmentally friendly and highly stable flux.
[0021] Preferably, in S3, the concentration of the phosphate buffer is 0.01-0.02 mol / L, and the pH is 6-6.5.
[0022] Preferably, in S3, the ultrasonic frequency is 10-15 kHz.
[0023] Preferably, in S5, the ultrasonic frequency is 12-18 kHz.
[0024] Beneficial effects:
[0025] The present invention adopts triethanolamine and cyclohexane citric acid compound, and under the synergistic effect of vaseline, can effectively prevent the flux from spreading to cause the formation of an oxide film on the surface of the welded part, thereby increasing the oxidation resistance of the flux.
[0026] The invention adopts tetraethyl orthosilicate and vinyl triethoxysilane for compounding, which not only has good dispersibility with phospholipids and cholesterol, but also is hydrophobic with tetraethyl orthosilicate and vinyl triethoxysilane, and is confined in the double-layer hydrophobic gap of phospholipids and cholesterol, and is in situ condensed to form vinyl-containing silicon balls after hydrolysis, and the formed activated silicon balls are initiated and copolymerized with linolenic acid and ethylenediamine to obtain polyamide silicon dioxide composite microspheres with vesicle structures, and the surfaces of the polyamide silicon dioxide composite microspheres have low cross-linking density grafting and present a linear chain structure, which can reduce the generation of bubbles and smoke in the welding process, effectively improve the stability of the system, and can significantly improve the wetting ductility of the flux when combined with lamellar structure brucite fibers.
[0027] The present invention adopts triethanolamine and cyclohexane citric acid, organic amines that meet environmental protection requirements, as active agents, and synergistically activates the effect of silicon balls. The slow-release effect of vesicles not only has long-lasting antioxidant properties and effectively improves the wettability of welding materials, but also better and more evenly wets the welding surface during the welding process, effectively enhancing the stability and insulation of the flux.
[0028] The present invention adopts rosin amine imidazoline as corrosion inhibitor, which is environmentally friendly. The hydrophobic and amine parts of the non-polar tricyclic structure of rosin amine are hydrophilic and have extremely high affinity with activated silicon balls. It can not only significantly increase the stability of the flux, but also has good insulation effect and mechanical properties.
[0029] The invention is not only environmentally friendly and has little odor, but also has good stability in practical applications, effectively enhances the storage stability of the system, improves the use effect of the soldering flux, and prolongs the service life. The preparation method is simple and suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a comparison chart of the wetting time of the environmentally friendly and highly stable soldering flux obtained using Example 5 and Comparative Examples 1-2.
[0031] Figure 2 The figure is a comparison chart of the wetting power of the environmentally friendly high-stable soldering flux obtained by using Example 5 and Comparative Examples 1-2.
[0032] Figure 3 It is a comparison chart of the expansion rate of the environmentally friendly and highly stable soldering flux obtained by using Example 5 and Comparative Examples 1-2.
[0033] Figure 4 This is a comparison chart of the insulation properties of the environmentally friendly and highly stable soldering flux obtained using Example 5 and Comparative Examples 1-2.
[0034] Figure 5 The stability comparison chart of the environmentally friendly high-stability soldering flux obtained by using Example 5 and Comparative Examples 1-2 is shown. DETAILED DESCRIPTION
[0035] The present invention will be further explained below in conjunction with specific embodiments.
[0036] The brucite fiber used below was purchased from Lingshou County Moujia Mineral Products Co., Ltd.; the cyclohexane citric acid used below was purchased from Dongguan Mouyu Chemical Co., Ltd.; the rosin amine imidazoline used below was purchased from Guangzhou Moubao Chemical Co., Ltd.; the coumarone resin used below was purchased from Wuhan Moulisheng Chemical Co., Ltd.
[0037] Example 1
[0038] A method for preparing an environmentally friendly and highly stable soldering flux comprises the following steps:
[0039] S1, 8g triethanolamine, 3g vaseline, 5g cyclohexane citric acid, 0.1g rosin amine imidazoline, and 5g methanol were mixed, and stirred at a temperature of 50°C for 20min to obtain preform a;
[0040] S2, 1g of coumarone resin and 5g of hydroxy acrylic resin were mixed, stirred at 100°C for 30min, cooled to 50°C, added to prefabricated material a and stirred evenly to obtain prefabricated material b;
[0041] S3, add 1g vinyl triethoxysilane, 2g ethyl orthosilicate, 1g cholesterol, 0.1g lecithin to 5g chloroform, stir evenly, remove chloroform by rotary evaporation, add to 0.01mol / L phosphate buffer solution with pH value of 6, ultrasonicate at 30°C for 1h, ultrasonic frequency of 15kHz, use extruder to pass through 100nm filter membrane to pH value of 9 ammonia solution, stand at 50°C for 15h, centrifuge, wash, and vacuum dry to obtain activated silica balls;
[0042] S4, adding activated silica balls and 0.1 g of diisopropylbenzene peroxide to 20 g of ethanol and stirring evenly, adding 0.5 g of linolenic acid and 0.5 g of ethylenediamine, reacting at 65° C. for 24 h under nitrogen protection, centrifuging, washing with water 3 times, and vacuum drying to obtain polyamide silica composite microspheres;
[0043] S5. Add 3 g of brucite fiber with a particle size of 20 nm and an aspect ratio of 20:1 and 0.5 g of sodium stearate into 5 g of water and stir for 1 h at a stirring speed of 300 r / min. Add silica composite microspheres and perform ultrasound at 50 °C for 1 h at an ultrasound frequency of 18 kHz. Cool to room temperature, filter, wash, vacuum dry, and crush. Add 1 g of hydrogenated castor oil and 1 g of zinc dichloride and preform b and mix well to obtain an environmentally friendly and highly stable flux.
[0044] Example 2
[0045] A method for preparing an environmentally friendly and highly stable soldering flux comprises the following steps:
[0046] S1, 10g triethanolamine, 5g vaseline, 8g cyclohexane citric acid, 1g rosin amine imidazoline, 4g ethyl acetate, 4g ethanol were mixed, and stirred at a temperature of 50°C for 20min to obtain preform a;
[0047] S2, 3g of coumarone resin and 8g of hydroxy acrylic resin were mixed, stirred at 100°C for 30min, cooled to 50°C, added to prefabricated material a and stirred evenly to obtain prefabricated material b;
[0048] S3, add 2g vinyl triethoxysilane, 6g ethyl orthosilicate, 2g cholesterol, 0.5g lecithin to 5g chloroform, stir evenly, remove chloroform by rotary evaporation, add to 0.01mol / L, pH 6 phosphate buffer, ultrasonicate at 30°C for 1h, ultrasonic frequency of 15kHz, use extruder to pass through 100nm pore size filter membrane to pH 9 ammonia solution, stand at 50°C for 15h, centrifuge, wash, and vacuum dry to obtain activated silica balls;
[0049] S4, adding activated silica balls and 0.3 g of diisopropylbenzene peroxide to 40 g of ethanol and stirring evenly, adding 1.5 g of linolenic acid and 1.5 g of ethylenediamine, reacting at 65 ° C for 24 h under nitrogen protection, centrifuging, washing with water 3 times, and vacuum drying to obtain polyamide silica composite microspheres;
[0050] S5. Add 5 g of brucite fiber with a particle size of 20 nm and an aspect ratio of 20:1 and 1 g of sodium stearate into 5 g of water and stir for 1 h at a stirring speed of 300 r / min. Add silica composite microspheres and perform ultrasound at 50 °C for 1 h at an ultrasound frequency of 18 kHz. Cool to room temperature, filter, wash, vacuum dry, and crush. Add 2 g of hydrogenated castor oil and 2 g of zinc dichloride and preform b and mix well to obtain an environmentally friendly and highly stable flux.
[0051] Implementation 3
[0052] An environmentally friendly and highly stable soldering flux and a preparation method thereof, comprising the following steps:
[0053] S1, 8.1g triethanolamine, 3.1g vaseline, 5.1g cyclohexane citric acid, 0.11g rosin amine imidazoline, 5.1g propylene glycol were mixed, and stirred at a temperature of 50°C for 20min to obtain preform a;
[0054] S2, 1.1g of coumarone resin and 5.1g of hydroxy acrylic resin were mixed, stirred at 100°C for 30min, cooled to 50°C, added to prefabricated material a and stirred evenly to obtain prefabricated material b;
[0055] S3, 1.1g vinyl triethoxysilane, 2.1g ethyl orthosilicate, 1.1g cholesterol, 0.11g lecithin were added to 5g chloroform, stirred evenly, chloroform was removed by rotary evaporation, added to a phosphate buffer solution with a concentration of 0.01mol / L and a pH of 6, ultrasonicated at a temperature of 30°C for 1h, an ultrasonic frequency of 15kHz, and passed through a filter membrane with a pore size of 100nm through an extruder to a pH of 9 ammonia solution, and allowed to stand at a temperature of 50°C for 15h, centrifuged, washed, and vacuum dried to obtain activated silica balls;
[0056] S4, adding activated silica balls and 0.1 g of diisopropylbenzene peroxide to 21 g of ethanol and stirring evenly, adding 0.51 g of linolenic acid and 0.51 g of ethylenediamine, reacting at 65° C. for 24 h under nitrogen protection, centrifuging, washing with water 3 times, and vacuum drying to obtain polyamide silica composite microspheres;
[0057] S5. Add 3.1 g of brucite fiber with a particle size of 20 nm and an aspect ratio of 20:1 and 0.5 g of sodium stearate into 5 g of water and stir for 1 h at a stirring speed of 300 r / min. Add silica composite microspheres and perform ultrasound at 50°C for 1 h at a frequency of 18 kHz. Cool to room temperature, filter, wash, vacuum dry, and crush. Add 1.1 g of hydrogenated castor oil and 1.1 g of zinc dichloride and preform b and mix well to obtain an environmentally friendly and highly stable flux.
[0058] Implementation 4
[0059] An environmentally friendly and highly stable soldering flux and a preparation method thereof, comprising the following steps:
[0060] S1, 9.9 g triethanolamine, 4.9 g vaseline, 7.9 g cyclohexane citric acid, 0.9 g rosin amine imidazoline, 3.9 g ethyl acetate, and 3.9 g ethanol were mixed, and stirred at 50° C. for 20 min to obtain preform a;
[0061] S2, 2.9 g of coumarone resin and 7.9 g of hydroxy acrylic resin were mixed, stirred at 100° C. for 30 min, cooled to 50° C., added to prefabricated material a and stirred evenly to obtain prefabricated material b;
[0062] S3, 1.9g vinyl triethoxysilane, 5.9g ethyl orthosilicate, 1.9g cholesterol, 0.49g lecithin were added to chloroform and stirred evenly, chloroform was removed by rotary evaporation, and the mixture was added to a phosphate buffer solution with a concentration of 0.01mol / L and a pH of 6, and ultrasonicated at a temperature of 30°C for 1h, and an ultrasonic frequency of 15kHz, and the mixture was passed through a filter membrane with a pore size of 100nm through an extruder to a pH of 9 ammonia solution, and the mixture was allowed to stand at a temperature of 50°C for 15h, centrifuged, washed, and vacuum dried to obtain activated silica balls;
[0063] S4, adding activated silica balls and 0.29g of diisopropylbenzene peroxide to 39g of ethanol and stirring evenly, adding 1.49g of linolenic acid and 1.49g of ethylenediamine, reacting at 65°C for 24h under nitrogen protection, centrifuging, washing with water 3 times, and vacuum drying to obtain polyamide silica composite microspheres;
[0064] S5. Add 4.9 g of brucite fiber with a particle size of 20 nm and an aspect ratio of 20:1 and 1 g of sodium stearate into water and stir for 1 h at a stirring speed of 300 r / min. Add silica composite microspheres and perform ultrasound at 50 °C for 1 h at an ultrasound frequency of 18 kHz. Cool to room temperature, filter, wash, vacuum dry, and crush. Add 1.9 g of hydrogenated castor oil and 1.9 g of zinc dichloride and preform b and mix well to obtain an environmentally friendly and highly stable flux.
[0065] Example 5
[0066] An environmentally friendly and highly stable soldering flux and a preparation method thereof, comprising the following steps:
[0067] S1, 9 g of triethanolamine, 4 g of vaseline, 6.5 g of cyclohexane citric acid, 0.5 g of rosin amine imidazoline, and 6 g of propylene glycol were mixed, and stirred at a temperature of 50° C. for 20 min to obtain preform a;
[0068] S2, 2 g of coumarone resin and 6.5 g of hydroxy acrylic resin were mixed, stirred at 100° C. for 30 min, cooled to 50° C., added to prefabricated material a and stirred evenly to obtain prefabricated material b;
[0069] S3, 1.5g vinyl triethoxysilane, 4g ethyl orthosilicate, 1.5g cholesterol, 0.3g lecithin were added to 5g chloroform and stirred evenly, chloroform was removed by rotary evaporation, and the mixture was added to a phosphate buffer solution with a concentration of 0.01mol / L and a pH of 6, and ultrasonicated at a temperature of 30°C for 1h, and an ultrasonic frequency of 15kHz, and the mixture was passed through a filter membrane with a pore size of 100nm through an extruder to a pH of 9 ammonia solution, and the mixture was allowed to stand at a temperature of 50°C for 15h, centrifuged, washed, and vacuum dried to obtain activated silica balls;
[0070] S4, adding activated silica balls and 0.2g diisopropylbenzene peroxide to 30g ethanol and stirring evenly, adding 1g linolenic acid and 1g ethylenediamine, reacting at 65°C for 24h under nitrogen protection, centrifuging, washing with water 3 times, and vacuum drying to obtain polyamide silica composite microspheres;
[0071] S5. Add 4 g of brucite fiber with a particle size of 20 nm and an aspect ratio of 20:1 and 0.7 g of sodium stearate into 5 g of water and stir for 1 h at a stirring speed of 300 r / min. Add silica composite microspheres and perform ultrasound at 50°C for 1 h at a frequency of 18 kHz. Cool to room temperature, filter, wash, vacuum dry, and crush. Add 1.5 g of hydrogenated castor oil and 1.5 g of zinc dichloride and preform b and mix well to obtain an environmentally friendly and highly stable flux.
[0072] Comparative Example 1
[0073] An environmentally friendly and highly stable soldering flux and a preparation method thereof, comprising the following steps:
[0074] S1, 9 g of triethanolamine, 4 g of vaseline, 6.5 g of cyclohexane citric acid, 0.5 g of rosin amine imidazoline, and 6 g of propylene glycol were mixed, and stirred at a temperature of 50° C. for 20 min to obtain preform a;
[0075] S2, 2 g of coumarone resin and 6.5 g of hydroxy acrylic resin were mixed, stirred at 100° C. for 30 min, cooled to 50° C., added to prefabricated material a and stirred evenly to obtain prefabricated material b;
[0076] S3, add 1.5g vinyl triethoxysilane and 4g ethyl orthosilicate to 5g chloroform, stir evenly, remove chloroform by rotary evaporation, add to 0.01mol / L phosphate buffer solution with a pH of 6, ultrasonicate at 30°C for 1h, ultrasonic frequency of 15kHz, use an extruder to pass through a 100nm pore size filter membrane to pH 9 ammonia solution, stand at 50°C for 15h, centrifuge, wash, and vacuum dry to obtain activated silica balls;
[0077] S4, adding activated silica balls and 0.2g diisopropylbenzene peroxide to 30g ethanol and stirring evenly, adding 1g linolenic acid and 1g ethylenediamine, reacting at 65°C for 24h under nitrogen protection, centrifuging, washing with water 3 times, and vacuum drying to obtain polyamide silica composite microspheres;
[0078] S5. Add 4 g of brucite fiber with a particle size of 20 nm and an aspect ratio of 20:1 and 0.7 g of sodium stearate into 5 g of water and stir for 1 h at a stirring speed of 300 r / min. Add silica composite microspheres and perform ultrasound at 50°C for 1 h at a frequency of 18 kHz. Cool to room temperature, filter, wash, vacuum dry, and crush. Add 1.5 g of hydrogenated castor oil, 1.5 g of zinc dichloride, 1.5 g of cholesterol, 0.3 g of lecithin, and preform b and mix well to obtain an environmentally friendly and highly stable flux.
[0079] Comparative Example 2
[0080] An environmentally friendly and highly stable soldering flux and a preparation method thereof, comprising the following steps:
[0081] S1, 9 g of triethanolamine, 4 g of vaseline, 6.5 g of cyclohexane citric acid, 0.5 g of rosin amine imidazoline, and 6 g of propylene glycol were mixed, and stirred at a temperature of 50° C. for 20 min to obtain preform a;
[0082] S2, 2 g of coumarone resin and 6.5 g of hydroxy acrylic resin were mixed, stirred at 100° C. for 30 min, cooled to 50° C., added to prefabricated material a and stirred evenly to obtain prefabricated material b;
[0083] S3, 1.5g vinyl triethoxysilane, 4g ethyl orthosilicate, 1.5g cholesterol, 0.3g lecithin were added to 5g chloroform and stirred evenly, chloroform was removed by rotary evaporation, and the mixture was added to a phosphate buffer solution with a concentration of 0.01mol / L and a pH of 6, and ultrasonicated at a temperature of 30°C for 1h, and an ultrasonic frequency of 15kHz, and the mixture was passed through a filter membrane with a pore size of 100nm through an extruder to a pH of 9 ammonia solution, and the mixture was allowed to stand at a temperature of 50°C for 15h, centrifuged, washed, and vacuum dried to obtain activated silica balls;
[0084] S4. Add 4 g of brucite fiber with a particle size of 20 nm and an aspect ratio of 20:1 and 0.7 g of sodium stearate into 5 g of water and stir for 1 h at a stirring speed of 300 r / min. Add activated silica balls, 0.2 g of diisopropyl peroxide, 30 g of ethanol, 1 g of linolenic acid, and 1 g of ethylenediamine. Ultrasonicate at 50°C for 1 h at a frequency of 18 kHz. Cool to room temperature, filter, wash, vacuum dry, and crush. Add 1.5 g of hydrogenated castor oil and 1.5 g of zinc dichloride and preform b and mix well to obtain an environmentally friendly and highly stable flux.
[0085] test
[0086] The environmentally friendly high-stability soldering fluxes prepared in Example 5 and Comparative Examples 1-2 were divided into Example 5 group and Comparative Examples 1-2 group, and the following tests were performed respectively.
[0087] Wetting performance test
[0088] After scrubbing and degreasing a 10mm×30mm×0.3mm pure copper sheet with a solvent, immerse it in a 10% hydrochloric acid solution for 5 seconds, take it out and wash it with running water, immerse it in anhydrous ethanol for a while, take it out and dry it, and hang it in a 120℃ oven for 1 hour. The wettability of the flux was tested using a Japanese SAT-5100 solderability tester, with a set temperature of 245℃, an immersion depth of 4mm, an immersion time of 5s, and an immersion speed of 5mm / s. After making sure that the tester is turned off, clamp a piece of treated pure copper sheet with a clamp, turn on the tester switch after clamping, and press the automatic test button to start measuring. At this time, the solder tank rises at a uniform speed of 5mm / s, stops when the pure copper sheet is immersed 4mm below the molten solder liquid level, and then stops for 5s, descends to the starting position at the same uniform speed of 5mm / s. During this period, the tester automatically tests the wetting time and maximum wetting force. Each flux is tested 5 times and the average value is taken. The test results are as follows Figure 1-2 As shown, the wetting time of Example 5 is the shortest and the wetting force is the largest, both of which are better than those of Comparative Examples 1-2.
[0089] Expansion rate test
[0090] Solder powder and flux were mixed in a ratio of 9:1 and mechanically stirred for 30 minutes to obtain solder paste. A copper clad laminate sample was prepared with a size of 25mm×25mm×1mm. After degreasing the surface of the copper clad laminate, the surface was polished with sandpaper, ultrasonically cleaned in anhydrous ethanol, and dried for later use. SACBN07 solder balls of uniform quality were prepared and the diameter of the solder balls was measured as D1. After reflow soldering, the height of the solder balls after spreading was measured as D2. The expansion rate was calculated according to the formula. The test results are as follows: Figure 3 As shown, the expansion rate of Example 5 group is the largest, which is better than that of Comparative Examples 1-2 groups.
[0091] Formula: E = (D2-D1) / D2×100%
[0092] D1: diameter of solder ball before soldering
[0093] D2: The height of the solder ball after wetting and spreading on the copper plate after welding
[0094] Insulation test
[0095] Take three Hang-type circuit boards as a group of test samples, clean them with pure water and deionized water, and then clean them with anhydrous ethanol or isopropanol. Keep the test pieces in an oven at 85°C for 30 minutes, take them out, and cool them to room temperature. Measure their insulation resistance and select a resistance value not less than 1x10 13 Ω test piece.
[0096] Before welding, apply flux evenly on three pieces of Hang-type test pieces, keep them in an 85℃ oven for 30 minutes, take them out, put them in a test box at 40℃ and a relative humidity of 90% to 95% for 96 hours, recover them at room temperature and a relative humidity of 90% for 1 hour, and use an insulation resistance tester to measure the insulation resistance between each point (read after 1 minute). Take the minimum value of the three test pieces as the insulation resistance before welding.
[0097] Insulation resistance after welding: Apply the flux sample evenly on the Hang type test piece, float it on the solder tank at 235℃+5℃ for 3s, then put it in a test box at 40℃ and relative humidity of 90-95% for 96h, recover it at room temperature and relative humidity of 90% for 1h, and use an insulation resistance tester to measure the insulation resistance between each point (read after 1min). Take the minimum value of the three test pieces as the insulation resistance after welding. The test results are as follows Figure 4 As shown, the insulation resistance of Example 5 is the largest, which is better than that of Comparative Examples 1-2.
[0098] Stability test
[0099] Solder powder and flux were mixed in a ratio of 9:1 and mechanically stirred for 30 minutes to obtain solder paste. After the solder paste was prepared, it was stirred for 2 minutes using a solder paste mixer to make the ingredients uniform. The viscosity was tested using a viscometer. The solder paste was placed in the viscometer and the test temperature was set to 25°C.
[0100] After the temperature stabilizes, set different speeds to observe the thixotropy and viscosity recovery of the solder paste. Record the measurement results. Store at 50°C for 30 days and use the same method to test the viscosity. The viscosity of the solder paste prepared with different fluxes before and after 30 days is obtained. The test results are as follows: Figure 5 As shown, the viscosity of Example 5 is the highest, which is better than that of Comparative Examples 1-2.
[0101] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An environmentally friendly and highly stable soldering flux, characterized in that: The raw materials include, by mass, 8-10 parts of triethanolamine, 3-5 parts of vaseline, 5-8 parts of cyclohexane citric acid, 0.1-1 parts of corrosion inhibitor, 5-8 parts of solvent, 1-3 parts of coumarone resin, 5-8 parts of hydroxy acrylic resin, 1-2 parts of vinyl triethoxysilane, 2-6 parts of ethyl orthosilicate, 1-2 parts of cholesterol, 0.1-0.5 parts of phospholipids, 0.1-0.3 parts of diisopropyl peroxide, 1-3 parts of polyamide monomer, 3-5 parts of brucite fiber, 0.5-1.0 parts of sodium stearate, 1-2 parts of hydrogenated castor oil and 1-2 parts of zinc dichloride.
2. The environmentally friendly and highly stable soldering flux according to claim 1, characterized in that: The corrosion inhibitor is rosin amine imidazoline.
3. The environmentally friendly and highly stable soldering flux according to claim 1, characterized in that: The solvent is at least one of methanol, ethanol, ethyl acetate and propylene glycol.
4. The environmentally friendly and highly stable soldering flux according to claim 1, characterized in that: The polyamide monomers include linolenic acid and ethylenediamine, and the weight ratio of linolenic acid to ethylenediamine is 1-2:1-2.
5. The environmentally friendly and highly stable soldering flux according to claim 1, characterized in that: The particle size of brucite fiber is 20-30nm, and the aspect ratio is 20-25:
1.
6. The environmentally friendly and highly stable soldering flux according to claim 1, characterized in that: The phospholipid is lecithin.
7. A method for preparing an environmentally friendly and highly stable soldering flux as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Mix triethanolamine, vaseline, cyclohexane citric acid, corrosion inhibitor and solvent, and stir at a temperature of 40-50° C. for 10-20 min to obtain preform a; S2, mixing coumarone resin and hydroxy acrylic resin, stirring at a temperature of 90-100° C. for 20-30 min, cooling to 40-50° C., adding to prefabricated material a and stirring evenly to obtain prefabricated material b; S3, adding vinyl triethoxysilane, ethyl orthosilicate, cholesterol, and phospholipids to chloroform, stirring evenly, removing chloroform by rotary evaporation, adding to phosphate buffer, ultrasonicating at a temperature of 10-30°C for 1-2h, using an extruder to pass through a filter membrane with a pore size of 100-500nm to a pH value of 8-9 ammonia solution, standing at a temperature of 50-60°C for 15-30h, centrifuging, washing, and vacuum drying to obtain activated silica balls; S4, adding activated silica balls and dicumyl peroxide to ethanol and stirring evenly, adding polyamide monomer thereto, reacting at a temperature of 65-75° C. for 20-24 h under nitrogen protection, centrifuging, washing with water 2-3 times, and vacuum drying to obtain polyamide silica composite microspheres; S5. Add brucite fiber and sodium stearate into water and stir for 1-2h, add silica composite microspheres, ultrasonicate at 40-50℃ for 1-2h, cool to room temperature, filter, wash, vacuum dry, crush, add hydrogenated castor oil, zinc dichloride and preform b and mix well to obtain environmentally friendly and highly stable flux.
8. The method for preparing an environmentally friendly and highly stable soldering flux according to claim 7, characterized in that: In S3, the concentration of phosphate buffer is 0.01-0.02 mol / L and the pH is 6-6.
5.
9. The method for preparing an environmentally friendly and highly stable soldering flux according to claim 7, characterized in that: In S3, the ultrasound frequency is 10-15kHz.
10. The method for preparing an environmentally friendly and highly stable soldering flux according to claim 7, characterized in that: In S5, the ultrasound frequency is 12-18 kHz.
Citation Information
Patent Citations
Lead-free solder thread-use colophony type non-halide cleaning-free scaling powder
CN101157168A
Environment-friendly no-clean soldering flux
CN104117787A
Environment-friendly soldering flux
CN108098189A
Resin-core soldering flux
CN103817461A
Silver paste composition and semiconductor device using same
CN104584140A
Cited By
Environment-friendly soldering flux material and preparation method thereof
CN121551914A